First Application of Whole Genome Sequencing in Myelinated Retinal Nerve Fibers (MRNF) - Scott Sills, E; Harrity, C; Chu, H I; Wang, J W; Wood, S H; Tan, S L (Physiological research, 2024)
Genetic features are currently unknown in myelinated retinal nerve fibers (MRNF). For a 20-year-old asymptomatic female with unilateral MRNF, we performed whole genome sequencing (WGS) by standard workflow protocol to produce contiguous long-read sequences with Illumina DNA PCR-Free Prep. After tagmentation, libraries were sequenced on separate runs via NovaSeq 6000 platform at 2 x 150bp read length. Gene variants included rs2248799, rs2672589, rs7555070, rs247616_T and rs2043085_C all associated with an increased macular degeneration risk, and seven novel variants of uncertain significance. For optic disc enlargement, variants rs9988687_A, rs11079419_T, rs6787363 and rs10862708_A suggested an increased risk for this condition. In contrast, modeling revealed retinal detachment risk was reduced by variants identified at rs9651980_T, rs4373767_T, and rs7940691_T which were among five other previously unreported variants. WGS data placed proband at the 66th and 64th percentiles for disc anomaly and retinal detachment risk, respectively. Additionally, risk determined from 16 loci associated with age-related macular degeneration found the patient to be at the 18th percentile for this diagnosis (i.e., below average genetic predisposition). Fundoscopic findings showed mean RNFL thickness was lower with MRNF (77 OS vs. 96?m OD) and RNFL symmetry was impaired (43 %) but stable between 2020 and 2023. Rim area and cup volume were also substantially different (2.33 OS vs. 1.34mm2 OD, and 0.001 OS vs. 0.151mm3 OD, respectively). As the first known evaluation of MRNF via WGS, these data reveal a mixed picture with variants associated with different risks for potentially related ocular pathologies. In addition, we identify multiple new variants of unknown significance. Factors affecting gene expression in MRNF require further study. Key words: Whole genome sequencing, Retina, Myelination, Anatomy, Gene variants.
Keywords: mladý dospělý; retina; lidé; Female; Young Adult; Nerve Fibers, Myelinated; nervová vlákna myelinizovaná; sekvenování celého genomu; genetická predispozice k nemoci; Whole Genome Sequencing; Retina; ženské pohlaví; Genetic Predisposition to Disease; Humans